Kajian Keluhan Pelayanan Ditinjau dari Kualitas Pelayanan Pasien Rawat Inap Peserta BPJS Non-PBI Kesehatan di RSU Puri Asih Salatiga - Dewi, Viny Natalia; Dewi, Ratih Kumala (Universitas Nasional Karangturi, 2022)
Management of hospital services needs to be done properly. This is to improve the quality of service and minimize complaints from patients. This study aims to determine the level of satisfaction of BPJS inpatients, identify service barriers, and provide service solutions at Puri Asih Hospital Salatiga. The method used by researchers using descriptive methods, through a qualitative approach. Data were collected through interviews, using a checklist interview guide with accidental sampling technique. The study was conducted from July to August 202. The samples used were 5 BPJS Health participant patients who received inpatient services, 2 authorized BPJS Health officers, and 5 inpatient service doctors through inclusion criteria. Some indicators of the service quality of inpatient BPJS participants for non-PBI health at RSU Puri Asih Salatiga in the poor category are the ease of achievement and adjustment of services, reliability and trust in BPJS service administration staff. Problems mostly lie in long service waiting periods, inadequate waiting room facilities such as small seats, and slow service speeds